2012
DOI: 10.1021/jo302283n
|View full text |Cite
|
Sign up to set email alerts
|

Clickable Di- and Tetrafunctionalized Pillar[n]arenes (n = 5, 6) by Oxidation–Reduction of Pillar[n]arene Units

Abstract: We report a new route for the selective synthesis of di- and tetrafunctionalized pillararenes via oxidation and reduction of the pillararene units. Hypervalent-iodine oxidation of perethylated pillar[5]arene afforded pillar[5]arene derivatives containing one benzoquinone unit and two benzoquinones at the A,B- and A,C-units. A pillar[6]arene derivative containing one benzoquinone unit was also synthesized. Reduction of the benzoquinone units yielded position-selective di- and tetrahydroxylated pillararene deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
95
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 54 publications
(21 reference statements)
1
95
0
1
Order By: Relevance
“…[16][17][18] These reported oxidations were performed in tetrahydrofuran (THF) in the presence of water, taking long reaction time to complete (24 h or 48 h). In order to improve yields and shorten reaction time, we re-investigated the partial oxidation of 1 by CAN (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18] These reported oxidations were performed in tetrahydrofuran (THF) in the presence of water, taking long reaction time to complete (24 h or 48 h). In order to improve yields and shorten reaction time, we re-investigated the partial oxidation of 1 by CAN (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, it was found that water is still needed like the reported oxidations. [16][17][18] The oxidation of 1 in pure CH 2 Cl 2 or CHCl 3 was hardly to go to complete even in extended reaction time (3 d) and the yields were very low. The structures of the oxidation products 2-5 were confirmed by the consistence of their NMR data and mass spectra (Supporting Information) with reported ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…68,69 Oxidation of a 1,4-dialkoxybenzene unit in per-alkylated pillar [5]arenes afforded pillar [5]arenes with a benzoquinone unit (19 [5] and 20 [5]). Benzoquinone was easily converted to hydroquinone using a reducing agent; thus, the A1/A2 dihydroxylated pillar [5]arenes (25[5] and 26 [5]) were obtained by reduction of the benzoquinone unit.…”
Section: Deprotection Of the Alkoxy Moieties Of Pillar[n]arenesmentioning
confidence: 99%
“…Furthermore, pillar [5]arenes with two benzoquinone units at the A/B (21 [5] and 22 [5]) and A/C (23 [5] and 24 [5]) units can be prepared under the optimized oxidation condition, and reduction of these pillar [5]arenes with two benzoquinone units led to A1/A2/B1/B2 (27 [5] and 28 [5]) and A1/A2/C1/C2 (29 [5] and 30 [5]) tetra-hydroxylated pillar [5]arenes. 68 Tuning the oxidation condition enables the synthesis of pillar [5]arenes with three and four quinone moieties. Xue et al reported the synthesis of pillar [5]arenes consisting of three different kinds of units by selective oxidation of the units (Scheme 12).…”
Section: Deprotection Of the Alkoxy Moieties Of Pillar[n]arenesmentioning
confidence: 99%